Exploitation of mobile devices in tracking construction projects using BIM - Mohamed Magd Eldin Mahmoud Adel Zaher; Mohamed Mahdy Marzouk (Cairo : Mohamed Magd Eldin Mahmoud Adel Zaher, 2016)
Augmented reality (AR) is used to explore a new era of integrating the building information modeling during project{u2019}s life cycle phases with the real world to enhance the interaction, considering different aspects of construction projects. This research proposes newly developed android applications that allow visualization, monitoring, construction planning, and facility management validated through case studies during the project life cycle. Augmented Reality is utilized during construction using an application named 2BIM-Phase3 through implementing a 4D model enhanced with an augmented video to show the 5D model powered with different cost parameters. Whilst, Facility Management takes place through another application named 2BIM-FM3 that is used to illustrate different types of assets information to avoid premature asset failure, and manage the required level of service. The third application is named 2BIM-Inspect3 that is used for inspection using augmented reality as a 3D model enriched the real-world environment showing the different systems such as firefighting, HVAC, plumbing networks. Finally, 2BIM-Track3 application is cloud-based which is able to export the progress into an Excel spreadsheet from the mobile application to a remote computer to update the project{u2019}s 5D model. 2BIM-Track3 android application is capable to be accessed to any uploaded project{u2019}s 3D model as well. Case studies are presented to illustrate the uses of the proposed applications
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Civil Engineering
Issued also as CD
Keywords: Augmented reality; Building information modeling; Construction projects tracking